Ultrasound-guided Open Nephron Sparing Surgery without Renal Artery Occlusion for Central Renal Tumors - 傅点 李平 徐锋 田丰 徐晓峰 位志峰 张征宇 葛京平 程文 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
From January 2008 to January 2013, 11 patients with central renal tumors underwent ultrasound-guided open nephron sparing surgery（ONSS） without renal artery occlusion. We removed the lesions, and the cut edges of the tumors were negative. Thus, we deduced that ultrasound-guided ONSS is suitable for the cases with obscure tumor boundary or multiple lesions. It could achieve the purpose of thoroughly removing lesions, as well as to expand the application range of nephron sparing surgery.